2021
DOI: 10.1080/22423982.2021.1935593
|View full text |Cite
|
Sign up to set email alerts
|

Differences between recorded diagnoses of patients of an emergency department and office-hours primary care doctors: a register-based study in a Finnish town

Abstract: To determine the extent to which it is possible to provide continuity of primary care for those who visit Emergency Departments (EDs) we studied how recorded diagnoses in primary care differ, depending on whether the patient is met in an ED or a primary care office-hours practice. In the present, 12-year follow-up study a report generator of the Electronic Health Record-system provided monthly figures for the number of different recorded diagnoses using the International Classification of Diagnoses (10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The study cohort is a representative sample of patients with T2D aged 60 years or older because of the integrity of the electronic patient record system in a single city, a publicly funded health care system, and inclusion of only older patients. During the follow-up, the proportion of GP appointments with a documented diagnosis in the collected dataset was at a good level (approximately 90%), as shown in a previous study using the same dataset where PHC visits and documented diagnosis were examined [ 23 ]. Inclusion of all GP and nurse appointments and not focusing on only T2D related appointments gives a more complete view of the utilization of PHC services.…”
Section: Discussionmentioning
confidence: 61%
“…The study cohort is a representative sample of patients with T2D aged 60 years or older because of the integrity of the electronic patient record system in a single city, a publicly funded health care system, and inclusion of only older patients. During the follow-up, the proportion of GP appointments with a documented diagnosis in the collected dataset was at a good level (approximately 90%), as shown in a previous study using the same dataset where PHC visits and documented diagnosis were examined [ 23 ]. Inclusion of all GP and nurse appointments and not focusing on only T2D related appointments gives a more complete view of the utilization of PHC services.…”
Section: Discussionmentioning
confidence: 61%
“…The 26 individuals who were evaluated as genuine emergencies were also excluded from the study, as mentioned in the literature. [ 14 ] Consequently, 325 patients were included in this study (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…[ 13 ] In Finland, a study on improving the recording of diagnoses in ES was designed equally well in the emergency department and office hours practices. [ 14 ] Studies have been conducted to determine the reasons for nonurgency visits of patients and have found that it is multidimensional. [ 2 , 15 , 16 ] This study aimed to investigate why patients chose to self-refer to the emergency department instead of their primary care health center for nonurgent complaints.…”
Section: Introductionmentioning
confidence: 99%
“…The finding that the proportions and numbers of simple infections in the ED decreased is in line with the aims of the interventions applied [ 2 4 ]. We knew that at least about 30% of the diagnoses done in the present kind of primary care ED system and office-hours primary care were the same and that office-hours primary care might therefore have provided better continuation of treatment for these patients than the ED [ 21 ]. Furthermore, when diagnoses in EDs and primary care doctor driven emergency systems have been compared, a higher prevalence of mild infections in primary care doctor driven emergency systems and a higher prevalence of injuries in EDs have been reported [ 22 ].…”
Section: Discussionmentioning
confidence: 99%